2011
DOI: 10.1016/j.jpba.2011.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of lysophosphatidic acids (LPAs) in human saliva and gingival crevicular fluid (GCF) by LC–MS/MS

Abstract: Lysophosphatidic acid (LPA) is a phospholipid mediator that plays multiple cellular functions by acting through G protein-coupled LPA receptors.LPAs are known to be key mediators in inflammation,and several lines of evidence suggest a role for LPAs in inflammatory periodontal diseases. A simple and sensitive liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) method has been developed and validated to quantify LPA species (LPA 18:0, LPA 16:0, LPA 18:1 and LPA 20:4) in human saliva and gingiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…For example, our group quantified bile acids in mouse liver, bile, plasma and urine, as well as human plasma and urine using charcoal stripping after demonstrating similar extraction recoveries from stripped matrices and original matrices for two stable-labeled isotope internal standards [8,10]. Similarly, we used charcoal-stripped human saliva for the quantification of four lysophosphatidic acids in saliva and gingival cervical fluids [82].…”
Section: Stripped Matricesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, our group quantified bile acids in mouse liver, bile, plasma and urine, as well as human plasma and urine using charcoal stripping after demonstrating similar extraction recoveries from stripped matrices and original matrices for two stable-labeled isotope internal standards [8,10]. Similarly, we used charcoal-stripped human saliva for the quantification of four lysophosphatidic acids in saliva and gingival cervical fluids [82].…”
Section: Stripped Matricesmentioning
confidence: 96%
“…Various approaches ( Figure 2) are followed to address the lack of blank matrices for the quantification of endogenous compounds by LC-MS/MS including, background subtraction [26-31], the standard addition method [24,25,[32][33][34][35][36][37][38][39][40][41][42][43][44], neat solutions [45][46][47][48][49][50][51][52], artificial matrices of biological fluids [23,, stripped matrices [8,10,11,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91], and surrogate analytes [66,[92][93][94][95][96][97]…”
Section: Approaches For Quantification Of Endogenous Analytesmentioning
confidence: 99%
“…LPA is present in all normal bodily fluids but contributes to pathology in different systems when levels are elevated 8 . The present authors have shown that LPAs 18:1, 18:0, and 16:0 are 10‐fold increased over normal (to pharmacologic levels) in the saliva and gingival crevicular fluid (GCF) of patients with moderate to severe periodontitis 9 …”
mentioning
confidence: 77%
“…The instrument specifications, software and setting conditions, mobile phase, and method validation have been reported previously; LPA calibration curves were prepared in serum‐free media as described 9 …”
Section: Methodsmentioning
confidence: 99%
“…is present in saliva, and becomes active in the tumor microenvironment 9) . The effects of LPA are mediated by several LPA receptors, which belong to the G protein-couple receptor class 10,11) .…”
Section: Introductionmentioning
confidence: 99%